Integrating Digital Literacy and Human Values as a Strategy for Addressing Challenges in the Digital Age in Indonesia - Tri Endah Prihandini; Harsasancaya Faiz Pramana; Rifky Ahmad Muhajirin; Puput Devi Apriliani; Nezah Dwi Anugrah; Selviana Nawang Wulandari; Galuh Wening Sekar Kuncoro; Muslimah Azzahra Hasibuhan; Arif Widagdo (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid expansion of digital technology has transformed social interaction, education, communication, and economic activities across Indonesia while simultaneously generating complex ethical and social challenges. This study examines the integration of digital literacy and human values as a strategic response to the demands of contemporary digital society. Employing a qualitative library research design, the study analyzes scholarly literature, policy documents, government regulations, and theoretical works related to digital literacy, information ethics, social development, and human centered technological transformation. The findings indicate that digital literacy extends beyond technical competence and encompasses critical evaluation, responsible information use, ethical awareness, and social accountability. The analysis further reveals that digital transformation contributes to challenges such as disinformation, declining empathy, online hostility, privacy concerns, and value disorientation, which may weaken social trust and civic responsibility. Human values grounded in ethical principles, character formation, Pancasila, and religious traditions function as essential safeguards against these risks. The study concludes that effective integration requires collaborative engagement among educational institutions, families, communities, religious organizations, and government agencies. Such an integrative framework strengthens digital competence, ethical resilience, and social trust, thereby supporting inclusive, sustainable, and human centered digital development in Indonesia.